Enteric Pathogenic Infection in Young Ghanaian Children and Associations with Iron-Deficiency and Anemia. (29th May 2020) - Lambrecht, Nathalie; Bridges, Dave; Adu, Bright; Wilson, Mark; Eisenberg, Joseph; Folson, Gloria; Baylin, Ana; Jones, Andrew
Abstract: Objectives: We aimed to determine the burden of Campylobacter infection among children in Greater Accra, Ghana and assess whether infection is associated with iron-deficiency and anemia. Methods: Blood and stool samples were collected from a random sample of 259 children aged 6 to 59 months residing in two districts in the Greater Accra Region, Ghana. Blood samples were analyzed for hemoglobin (Hb) concentration, the iron status biomarkers serum ferritin (SF) and serum transferrin receptor (sTfR), and the inflammatory biomarkers C-reactive protein (CRP) and α-1-acid glycoprotein (AGP). Anemia was defined as Hb < 11.0 g/dL and iron-deficiency as SF < 12 µg/L or sTfR > 8.3 mg/L. We used quantitative polymerase chain reaction (qPCR) to analyze bacterial DNA from stool samples for Campylobacter species. Multivariate logistic regression was used to assess child- and household-level predictors of infection. Results: Overall, 16.2% of children were positive for Campylobacter infection, with the highest infection prevalence among children under two years old. Children positive for Campylobacter infection had 3.4 times higher odds of elevated CRP levels (95% CI: 1.66, 7.05) and 3.0 times higher odds of elevated AGP levels (95% CI: 1.61, 5.76), after adjusting for child age and sex, vitamin A deficiency, malaria, and household sanitation and wealth. Campylobacter infection was associated with 2.5 times higher odds of low SF (95% CI: 1.20, 5.12) and marginally higher odds of elevated sTfR (OR: 2.10, 95% CI: 0.96, 4.58), but was not significantly associated with higher odds of anemia (OR: 1.15, 95% CI: 0.69, 1.93). Ownership of small livestock, including goats, sheep, and pigs, but no other livestock, was associated with Campylobacter infection. Conclusions: Our results suggest that Campylobacter infection contributes to the inflammatory burden among young children in Ghana and that infection may also negatively affect iron status. Furthermore, livestock may contribute to infectious pathogen exposure. Funding Sources: University of Michigan (U-M) International Institute, U-M Office of Global Public Health, U-M African Studies Center, U-M Rackham Graduate School, U-M Nutritional Sciences Department, the Dow Chemical Company Foundation through the Dow Sustainability Fellows Program at the University of Michigan.